Environmental impact assessment of the sewage outfall at Davis Station, East Antarctica - J Stark; C King; M Riddle; I Snape; M Lindsay; S Stark; G Johnstone; J Smith; M Powers; Trish Corbett; Julie Mondon; R Leeming (2011)
During the summer 2009/10, an environmental impact assessment of the sewage outfall was conducted at Davis Station, East Antarctica. An investigation of the nature and extent of impacts to the marine environment associated with current sewage treatment and effluent discharge practices included ecological surveys of macrobiological communities, physico-chemical analysis of sediments and receiving waters, microbiological analysis, and histopathological analysis of fish. Ecotoxicological testing using local invertebrates to determine effluent toxicity was interpreted alongside dispersal modelling data of the discharge plume to determine the potential extent of impacts and inform recommendations on the level of treatment and dilution of sewage required to minimise impacts. No evidence of impacts was detected on soft sediment infaunal or epifaunal communities, and only low levels of contamination and accumulation were found in sediments and waters in the immediate vicinity of the outfall and in the direction of primary current flow. In contrast, sterol biomarkers and faecal coliforms ( E. coli ) were detected in sediments collected adjacent to the outfall and in most water column samples. Marine invertebrates ( Abatus and Laternula ) also tested positive for E. coli and antibiotic resistance mechanisms were present in Laternula indicating the introduction and dispersal through the water column of foreign microbes and bacteria associated with human effluent. Fish ( Trematomus bernacchii ) close to the outfall showed significant histological alterations in all major tissues (liver, gill, gonad, muscle) resulting from exposure to sewage. Effluent was toxic to amphipods ( Paramoera walkeri ) and microgastropods ( Skenella paludionoides ), with reduced survival in concentrations as low as 3.125% over a 21d exposure period. Acute effects were also observed in both species following 24h exposure, with 100% mortality at the highest effluent concentrations tested (68%). The application of these results to support and guide ...